Older Adult and Surrogate Perspectives on Serious, Difficult, and Important Medical Decisions. Issue 8 (4th July 2018) - Petrillo, Laura A.; McMahan, Ryan D.; Tang, Victoria; Dohan, Daniel; Sudore, Rebecca L.
Abstract : Objectives: To elicit decisions that diverse older adults and surrogates perceive as serious, difficult, or important and explore what helped them make those decisions. Design: Focus groups (N=13) in which participants were asked to recall serious, difficult, or important medical decisions and what helped them make those decisions. Setting: Clinics, support groups and senior centers. Participants: Diverse English‐ and Spanish‐speaking older adults (age: mean 78, range 64–89) and surrogates (age: mean 57, range 33–76) (29% African American, 26% white, 26% Asian or Pacific Islander, 19% Hispanic) (N=69). Measurements: We used thematic analysis to analyze transcripts. Results: We identified 168 decisions. Older adults from all racial and ethnic groups frequently recalled cancer treatment decisions and decisions about chronic illness management. Surrogates described decisions about transitions in care and medical crises. Older adults valued self‐sufficiency and maximizing survival and relied on personal experiences as often as medical advice. In all racial and ethnic groups, surrogates valued avoiding suffering for loved ones. Conclusion: Diverse older adults and surrogates perceive life‐threatening illness and day‐to‐day decisions about chronic disease to be serious, difficult, and important. The surrogates' goal of avoiding suffering of older adults may differ from older adults' priorities of self‐sufficiency and maximizing survival. Clinicians should support older adults and surrogates in identifying important and difficult decisions and learn about the values and information sources they bring to decision‐making. With this knowledge, clinicians can customize decision support and achieve person‐centered care.